WILLINGNESS TO PAY WARUNG MAKAN TERHADAP TPS 3R DI DESA BABAKAN KABUPATEN BOGOR - Ni Putu Manacika Manupada; Ahyar Ismail; Meti Ekayani (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2019)
Babakan is one of administrative villages in Bogor Regency where Institut Pertanian Bogor (IPB) is located. IPB has given social and economic impacts in Babakan that many small-scalled business developed and small-scalled restaurant has the most participators. These small-scale restaurants generate waste everyday and the waste is still managed with end of pipe practice where waste was hauled from collection point to disposal site without any intermediate treatment. Community based waste management with 3R (reduce, reuse, recycle) approach should be proposed to reduce waste at source. 3R Solid Waste Treatment Facilities (TPS 3R) is a facility that focused on reducing, reusing, and recycling waste at source comunally involved active roles from community and goverment. The objectives of this study are (1) Examining level of participation of small-scale restaurant owners if TPS 3R is built and implemented in Babakan. (2) Estimating Willingness to Pay (WTP) of small-scale restaurans owners to TPS 3R implementation planning. The results showed most of small-scale restaurant owners are willing to participate in both sorting waste at source and paying TPS 3R service if TPS 3R is being implemented in Babakan. Average WTP values for TPS 3R is Rp 32,037.04/month and it’s higher than existing rate of waste collection service, which shows small-scale restaurant owners have preference for TPS 3R. Keywords: small-scaled restaurants; TPS 3R; waste management; willingness to pay